2021
DOI: 10.1038/s41598-021-95048-w
|View full text |Cite
|
Sign up to set email alerts
|

Handler familiarity helps to improve working performance during novel situations in semi-captive Asian elephants

Abstract: Working animals spend hours each day in close contact with humans and require training to understand commands and fulfil specific tasks. However, factors driving cooperation between humans and animals are still unclear, and novel situations may present challenges that have been little-studied to-date. We investigated factors driving cooperation between humans and animals in a working context through behavioural experiments with 52 working semi-captive Asian elephants. Human-managed Asian elephants constitute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In experiments based on the same population of horses as in this study, Liehrmann et al ( 2022 ) found that older horses agreed more often to walk on a novel surface when led by someone familiar than someone unfamiliar, and horses with longer relationship with their owner performed less reluctant behaviours towards the novel objects than horses having shorter relationship with their caretaker. Similarly, working Asian elephants agreed more often to step on a novel surface with and handler they knew for more than a year (Liehrmann et al 2021 ). In our study, the experiment involved free participation from the horses and included food reward so the informant was probably quickly associated with something positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experiments based on the same population of horses as in this study, Liehrmann et al ( 2022 ) found that older horses agreed more often to walk on a novel surface when led by someone familiar than someone unfamiliar, and horses with longer relationship with their owner performed less reluctant behaviours towards the novel objects than horses having shorter relationship with their caretaker. Similarly, working Asian elephants agreed more often to step on a novel surface with and handler they knew for more than a year (Liehrmann et al 2021 ). In our study, the experiment involved free participation from the horses and included food reward so the informant was probably quickly associated with something positive.…”
Section: Discussionmentioning
confidence: 99%
“…One way to be more specific is to consider the relationship length between the familiar person and the animal. In working Asian elephants, the relationship length affected the elephants’ response in test situations; the elephants agreed more often to step on a novel surface and responded faster when they were called by a familiar handler whom they had known for a longer time (Crawley et al 2021 ; Liehrmann et al 2021 ). In horses, recent findings from Liehrmann et al ( 2022 ) show that older horses agreed more often to walk on a novel surface when led by someone familiar than someone unfamiliar, and in general horses with a longer relationship with their owner were less scared of novelty than horses having a shorter relationship with their handler.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between care staff familiarity and positive impacts has also been demonstrated in other species. For instance, more established care staff to animal relationships were associated with increased willingness to embrace new surfaces [ 38 ] and successful task completion [ 39 ] in Asian elephants ( Elephas maximus ). While a more in-depth study is needed to quantify the effect of increased contact with care staff on the physiological changes associated with dramatic habitat differences, we believe that the intense care and positive relationships provided by our care staff may have helped to buffer the orangutans from the potential stressful effects of the two moves and housing changes.…”
Section: Discussionmentioning
confidence: 99%
“…Strong ties between mahouts and elephants also can predict levels of cooperation. When elephants were asked to cross a novel surface (low bridge), those that had worked with their handler for over a year were more willing to cross it than those with a shorter relationship (66). Likewise, elephants responded more, and faster, in behavioral tasks in response to mahouts they had known longer (63).…”
Section: Mahout Management and Attitudementioning
confidence: 99%